(untitled) (Mustansiria Dental Journal, 2018)
The function of flap is to raise the soft tissue overlying the surgical site to give the best possible view to the operator and sufficient exposure of the area to be operated on with minimal postoperative complications. The objective of this study is to evaluate a new flap design for exposure of periapical lesion, also to compare it with other common flaps used in periapical surgery. The study include 107 young patients apicectomized for one, two, or three anterior teeth from January2007 to June 2008, age ranged between 18-30 years old, using special case sheet. The flap has given good access to one, two or three apices apicectomized with less postoperative complications including pain, swelling, parasthesia of lip and wound healing. The flap described is an alternative approach to reach the periapical area that may be used to overcome the disadvantages of other flap designs used in periapical surgery.